1998
DOI: 10.1063/1.122237
|View full text |Cite
|
Sign up to set email alerts
|

Rapid imaging of calcite crystal growth using atomic force microscopy with small cantilevers

Abstract: Using a 26 μm cantilever with a resonant frequency of 100 kHz in water, we were able to obtain sequential images of calcite crystal steps growing from a screw dislocation. The small cantilever permitted acquisition of 250 nm images at scan rates of 104 lines/s (1.2 s/image). From this sequence we directly measured critical step lengths (the length of the shortest step that can advance) of 6–21 nm. These values provided a rough estimate of (0.25±0.13 J/m2) for the step energy per unit length per unit step heigh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
49
0

Year Published

2003
2003
2016
2016

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 72 publications
(51 citation statements)
references
References 25 publications
2
49
0
Order By: Relevance
“…So far, applications of small cantilevers have mainly been focused on the highspeed imaging in liquid using amplitude modulation AFM (AM-AFM) [24,16,25]. These previous works demonstrated the improved time response of dynamic-mode AFM obtained by the small cantilevers.…”
Section: Introductionmentioning
confidence: 99%
“…So far, applications of small cantilevers have mainly been focused on the highspeed imaging in liquid using amplitude modulation AFM (AM-AFM) [24,16,25]. These previous works demonstrated the improved time response of dynamic-mode AFM obtained by the small cantilevers.…”
Section: Introductionmentioning
confidence: 99%
“…This makes probes with high (300 kHz or greater) resonant frequencies very desirable so that the number of pixels measured per second is high (500 s−1 or greater) and imaging times remain small (10 minutes or less for a typical 512 × 512 image). [42][43][44][45][46] Detection system Numerous detection systems have been developed to measure the motion of the cantilever. By far the most popular is an optical method commonly referred to as optical beam deflection47-49 (see Fig.…”
Section: Probe Designmentioning
confidence: 99%
“…[27][28][29][30][31][32] Especially, De Yoreo et al have shown that it is possible to change the shape of calcite by adding, e.g., magnesium or acidic amino acids to the growth solution of calcite. 33,34 In this paper we want to image calcite in liquids, because it provides atomic resolution.…”
Section: Measurements In Liquid On Calcitementioning
confidence: 99%